Al Jazeera’s Media Framing of the Humanitarian Crisis in Rafah 2024 - Ayuningtyas, Valendira Puspita; Nursita, Rizki Dian (Jisiera: The Journal of Islamic Studies and International Relations, 2026)
Framing is a method used by the media to present ideas or perspectives on an issue in a way that can influence how people think. Using Robert Entman’s framing theory, this study analyzes how Al Jazeera framed its news coverage of the violence in Rafah in 2024, which led to a humanitarian crisis. This study employs qualitative content analysis as its research method and adopts Entman’s framing model, which comprises four analytical elements: defined problems, diagnosed causes, moral judgment, and treatment/recommendation. The findings reveal that the main issues highlighted were the humanitarian situation in Rafah and Israel’s planned ground invasion. The causes of these problems were identified as Israeli military attacks, access restrictions imposed by Israel, and stalled ceasefire negotiations. In the moral judgment aspect, Al Jazeera emphasized support for Palestine and a negative judgment on Israel. Furthermore, in the treatment/recommendation dimension, Al Jazeera urged the international community to continue warning Israel against attacking Rafah and to pursue ceasefire negotiations. Lastly, the UN Security Council’s emergency meeting was also featured by Al Jazeera as a key recommendation in its reporting.